2014
DOI: 10.3390/ijerph110707275
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Body Mass Index, and Cardiorespiratory Fitness among School Children in Taiwan: A Cross-Sectional Study

Abstract: There is evidence that cardiorespiratory fitness and physical activity significantly reduce cardiovascular risks in adults. A better understanding of the association between cardiorespiratory fitness, physical activity, and childhood obesity is vital in assessing the benefits of interventions to prevent obesity. This study was to examine the relationship between physical activity, body mass index, and cardiorespiratory fitness levels in Taiwanese children. A cross-sectional study was designed. Study participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 35 publications
2
35
0
12
Order By: Relevance
“…The results of this study demonstrated that the prevalence of overweight and obesity among school children of both sexes (boys: 36.3%; girls: 25.5%) from the southern county of Taiwan was high than the prevalence of these conditions reported among a similar group of school children (boys: 34.0%; girls: 25.0%) in 2011 [19] and significant higher than that found in the national survey in Taiwan 2012 (boys: 31.70%; girls: 25.1%) [20]. Given the combined high prevalence of overweight and obesity among southern Taiwanese youth, especially boys, we thus argue that this problem requires immediate health promotion intervention.…”
Section: Discussionmentioning
confidence: 86%
“…The results of this study demonstrated that the prevalence of overweight and obesity among school children of both sexes (boys: 36.3%; girls: 25.5%) from the southern county of Taiwan was high than the prevalence of these conditions reported among a similar group of school children (boys: 34.0%; girls: 25.0%) in 2011 [19] and significant higher than that found in the national survey in Taiwan 2012 (boys: 31.70%; girls: 25.1%) [20]. Given the combined high prevalence of overweight and obesity among southern Taiwanese youth, especially boys, we thus argue that this problem requires immediate health promotion intervention.…”
Section: Discussionmentioning
confidence: 86%
“…Inclusive, existe evidencia científica de que la obesidad en la etapa preescolar estuvo asociada con un pobre desempeño físico (26). En el presente estudio el VO2 MAX fue menor en los sujetos con obesidad en comparación con los otros grupos de estudio, similar a los hallazgos encontrados en niños obesos, los cuales eran más propensos a carecer de una aptitud cardiorrespiratoria adecuada medida a través de un test de carrera de 800 metros (27). Una disminución de la capacidad residual funcional fue la anormalidad más común en la función pulmonar reportada en un estudio desarrollado en niños y adolescentes obesos (28).…”
Section: Discussionunclassified
“…17 Resultados similares foram encontrados em Taiwan, onde crianças fisicamente mais ativas possuem melhores níveis de aptidão cardiorrespiratória (29,6%). 18 A tabela 2 demonstra os fatores associados ao sobrepeso/obesidade, de acordo com o sexo. Observa-se que o deslocamento motorizado para a escola esteve associado ao sobrepeso/obesidade, tanto nos meninos (RP: 1,30; p<0,001), quanto nas meninas (RP: 1,16; p=0,021).…”
Section: Resultsunclassified